Potensi Cadangan Karbon Tersimpan dan Serapan Karbon pada Ekosistem Hutan Kota Tinjomoyo Semarang - Nur Puji Lestari; Nana Kariada Tri Martuti (Life Science, 2024)
The increase in GHGs in Semarang City, caused by the increase in motorized vehicles and industrial activity, has resulted in a decrease in environmental quality in urban areas and air pollution. Data from the Semarang City Environmental Service (2019), shows that total CO2e emissions in 2018 were dominated by CO2, namely 33,505,357.22 tons of CO2 (85.24%) of the total CO2e tons of GHG emissions. To reduce CO2 emissions in Semarang City, one way that can be done is by utilizing urban forests which can absorb carbon dioxide. Based on these conditions, estimates of stored carbon reserves and carbon uptake in urban forests need to be calculated to determine the CO2 that plants in urban forests can absorb. This research aims to analyze the amount of stored carbon reserves and carbon uptake in the Tinjomoyo Semarang City Forest ecosystem. This research uses an exploratory method carried out through direct observation and measurement in the field. The sampling technique used is the belt transect method. The stand measurement method is carried out using the Non-Destructive Test (NDT) method or by not damaging the research samples. Stand data analysis was carried out using the allometric equation method. Based on calculation results, the number of individual stands in the Tinjomoyo Semarang City Forest area is 367 individual stands. The total amount of biomass is 125.5 tonnes/ha, the total carbon stock is 57.72 tonnes/ha and the total amount of carbon uptake is 211.8 tonnes/ha. This research shows that the estimated carbon reserves stored in the Tinjomoyo City Forest ecosystem, Semarang are 57.72 tonnes/ha with a carbon uptake value of 211.8 tonnes/ha.